Narasi Fikih Kebangsaan di Pesantren Lirboyo - Achmad Hidayat; Zaenal Arifin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article reviews the idea of ​​a nationalist Islamic boarding school in Lirboyo Kediri. This idea was born after the bahstul Masa'il was carried out by the Lirboyo Islamic Boarding School Alumni Association (Himasal) by responding to issues that occurred in this country. The method used is referring to the results of the Alim Ulama National Conference regarding methods of law-making, including qauli, ilhaqi, and manhaji. Indirectly, in an academic context, this national fiqh is a branch, or further study of scientific discussion in the form of Nusantara fiqh, which Nusantara fiqh is also a further specification of Nusantara Islam. Within the pesantren itself, the idea of ​​national fiqh is narrated in the form of a book that is disseminated, discussed and publicized, and used as the subject of the pesantren. So that it can be seen, from here that the Lirboyo pesantren has an orientation to contribute to national problems, namely the issue of nationality. The results show that the idea of ​​national fiqh in the Lirboyo Islamic boarding school emerged on the basis of the anxiety experienced by the alumni of the Pesantren Lirboyo. This idea manifests itself in the form of: a). the book that was distributed. b). discussed in a public seminar. c). used as subjects in the pesantren.